A Framework for Assessing Green Growth Policies - de Serres, Alain (OECD Economics Department Working Papers, 2010)
This paper proposes an analytical framework for assessing policies that will contribute to a better integration of environmental externalities in the pursuit of economic efficiency and growth objectives. The framework consists of two parts. The first part lays out principles and criteria for the identification and selection of policies that will benefit both income and the environment or that will boost income at the least cost in terms of the environment (and vice-versa). In general putting a price on a pollution source or on the over-exploitation of a scarce resource is found to be the most efficient single policy to address many environment externalities. However, given that environmental damage often result from several interacting market failures, an appropriate policy response will in many cases involve a mix of complementary instruments. The second part focuses more on issues of structural adjustment related to the transition towards a greener economy. It finds that green growth policies could lead to significant re-allocation of resources within and across broad economic sectors. A policy framework facilitating the re-deployment of labour across firms and sectors, as well as the entry of new firms and the exit of firms in declining industries will thus be important in order for countries to seize the opportunities brought about by green growth policies